Acute Pancreatitis Following Doxycycline and Ornidazole Coadministration - Ocal, Serkan; Selçuk, Haldun; Korkmaz, Murat; Unal, Hakan; Yilmaz, Uğur (JOP. Journal of the Pancreas, 2010)
Context Drugs are related to the etiology of acute pancreatitis in approximately 1.4-2.0% of cases. Although antibiotics constitute a small number of the drugs suspected, tetracycline is the most encountered antibiotic among those drugs. Case report A 33-year-old woman was admitted to the emergency room complaining of nausea and abdominal pain after the use of doxycycline 500 mg and ornidazole 500 mg twice daily for three days for a vaginal infection. She experienced epigastric pain, which worsened over time and radiated to her back. After a detailed evaluation, she was diagnosed as having mild acute pancreatitis which improved with medical treatment. All other possible causes of pancreatitis were eliminated. Conclusions Antibiotic-associated pancreatitis usually has a silent and mild course. To the best of our knowledge the literature reports only two cases of doxycycline-induced acute pancreatitis reported and there are no reports of pancreatitis associated with ornidazole. Our case is the first case reported in which doxycycline and ornidazole coadministration induced acute pancreatitis. Image: Baskent University. Ankara, Turkey.